PENGARUH PENGALAMAN KERJA, UPAH TENAGA KERJA DAN MODAL TERHADAP PRODUKTIVITAS INDUSTRI KECIL KONVEKSI DI KOTA DENPASAR - Antarawan, Nyoman Yushea; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Small industries have a good future due to their superiority in absorbing labor. The development of small industries will help overcome the problem of unemployment given the high unemployment in urban areas. Small industries open up business fields, which in turn encourage regional development. Convection as one of the small industries needed by the community in meeting the needs of clothing has relatively large market opportunities and competition and can encourage economic growth. The purpose of this study was to analyze the effect of work experience, labor and capital wages simultaneously and partially on the productivity of small industrial convection in the city of Denpasar. The sample determination method used is using proportionale random sampling. The number of samples in this study were 87 convection business units obtained using the Slovin formula.The data collected is processed by multiple linear regression analysis. The results showed that work experience, labor wages and capital simultaneously had a significant effect on the productivity of small convection industries in Denpasar City. Work experience, labor wages and capital partially have a positive and significant effect on the productivity of small convection industries in the city of Denpasar. Keywords : Productivity, Work Experience, Labor Wages, Capital labor